PEMBERIAN BEBERAPA TAKARAN KOMPOS BAGLOG JAMUR TIRAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) - Tri Yuda Putra; Yusnaweti Yusnaweti; Yustitia Akbar (Ensiklopedia of Journal, 2025)
The research entitled "Giving Several Doses of Oyster Mushroom Baglog Compost to the Growth and Yield of Sweet Corn Plants (Zea mays saccharata) has been carried out in a research field of the Faculty of Agriculture, University of Muhammadiyah West Sumatra (UMSB), Tanjuang Gadang Koto Nan Ampek Village, West Payakumbuh District, Payakumbuh City, with a type of inceptisol soil, and has an altitude of ± 514 meters above sea level. The research was conducted from July to September 2024. The purpose of this study is to obtain the best dose of oyster mushroom baglog compost for the growth and yield of sweet corn plants.This study used a Group Random Design (RAK) with 5 treatments of 4 groups, so that there were 20 experimental plots with a size of 1.2x 1.2 cm. In each plot there are 6 plants, 3 plants are used as sample plants. The treatment given is the size of Oyster mushroom baglog compost 0 tons/ha, the dosage of 10 tons/ha, the dosage of 20 tons/ha, the dosage of 30 tons/ha, the dosage of 40 tons/ha. The observation data were averaged and statistically analyzed with the F test at a real level of 5%. The observations made were plant height, number of leaves, leaf length, leaf width, number of cobs, length of cobs, plant weight, weight of plots, weight per hectare of sweet corn plants.From the results of this study, it can be concluded that the administration of several doses of oyster mushroom baglog compost has not been able to increase the growth and yield of sweet corn plants.Keywords: Sweet corn, Oyster mushroom baglog compost, Dosage